2015
DOI: 10.1007/s13224-014-0666-5
|View full text |Cite
|
Sign up to set email alerts
|

Materno-Fetal Outcomes with Viral Hepatitis in Pregnancy

Abstract: Objective To evaluate materno-fetal outcomes in pregnant women with jaundice. Methods A prospective study was conducted over a period of 6 months in a tertiary care hospital of Delhi, India. 82 pregnant women with jaundice were included. The serum was screened for viral markers, liver function tests, and coagulation status. Results The mean age of women was 27.3 ± 4.3 years. 43.9 % (n = 36) women were HEV positive, 36 % (n = 27) HBsAg positive, 4 % (n = 3) HAV positive and 1.3 % (n = 1) HCV positive. Intrahepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
(24 reference statements)
1
13
0
Order By: Relevance
“…6 This high number of preterm deliveries is also in congruence with the study reported by Singla et al wherein the proportion of preterm deliveries was 76%. 3 The majority (54.1%) of the patients were primigravidae. This is comparable to the results reported by Sultana et al, wherein 40% of the patients were primigravidae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 This high number of preterm deliveries is also in congruence with the study reported by Singla et al wherein the proportion of preterm deliveries was 76%. 3 The majority (54.1%) of the patients were primigravidae. This is comparable to the results reported by Sultana et al, wherein 40% of the patients were primigravidae.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the approach followed by Singla et al, wherein also the rate of induction was small, at 25%. 3 Majority (63%) of the babies were in the range of birthweight 1 to 2.5kg; and average birth weight of neonate was 1.6kg. Perinatal mortality was 33%, which was accounted for by 5 fresh still births and 2 macerated still births.…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics are similar to the first outbreak of HEV in Delhi. 24,25 This suggests that there is no change in the epidemiological pattern of hepatitis E outbreak observed in Shimla.…”
Section: Pregnancy and Hepatitismentioning
confidence: 96%
“…The mortality rates due to HEV in pregnancy vary from 0 to 13.88% in recent studies. 24,25 The Shimla hepatitis outbreak was predominantly hepatitis E outbreak. The characteristic features of the hepatitis E epidemic were (i) point source epidemic transmitted by fecally contaminated drinking water supply, (ii) involvement of a large population, (iii) high attack rate in young adults and (iv) high mortality in pregnant women with term pregnancies.…”
Section: Pregnancy and Hepatitismentioning
confidence: 99%
“…Early symptoms and clinical features among pregnant patients are similar to nonpregnant patients, however, there is a high risk of rapid progression to poor maternal, obstetric and foetal outcome. These include deranged coagulogram, encephalopathy, death, intra-uterine death and premature deliveries [15][16][17][18][19]. Understanding mechanism(s) of disease severity and mortality in pregnant women is of utmost importance and relevance for the endemic countries.…”
mentioning
confidence: 99%